Museum Permainan Tradisional sebagai Media Pembelajaran Nilai-Nilai Pancasila - Shidiq, Muhammad; Zaini Alif, Mohamad (PANGGUNG, 2025)
Learning media is an important element of the educational process. However, contemporary education tends to place less emphasis on values and character development. Most learning media are developed primarily for content delivery, with limited attention to attitudinal or character-building dimensions. Therefore, this study examines the use of traditional toy museums as a medium for learning Pancasila values. Traditional toy museums were selected for their effectiveness as learning media, especially in teaching culture and human values. This study employed a qualitative method using purposive sampling and a naturalistic approach, with visitors to the traditional toy museum as the research subjects. The research data was obtained through questionnaires, interviews, and observations. By integrating museums and traditional toys, this study aims to create a learning medium that not only delivers content but also effectively instills values. The results of this study provide a theoretical basis for positioning museums as learning media for students in both formal and non-formal contexts.